Demand for redistribution: Individuals' response to economic setbacks - Linna Martén (Uppsala University, Department of Economics, 2017)
Although economic circumstances have been argued to be a major determining factor of attitudes to redistribution, there is little well identified evidence at the individual level. Utilizing a unique dataset, with detailed individual information, provides new and convincing evidence on the link between economic circumstances and demand for redistribution (in the form of benefits and support). The Swedish National Election Studies are constructed as a rotating survey panel, which makes it possible to estimate the causal effect of economic changes. The empirical analysis shows that individuals who experience a job loss become considerably more supportive of redistribution. Yet, attitudes to redistribution return to their initial level as economic prospects improve, suggesting that the effect is only temporary. Despite the fact that a job loss also changes attitudes to the political parties, the probability to vote for the left-wing is not affected.
urn:nbn:se:uu:diva-314113
Keywords: D31; H55; D72; J64; 330; Redistribution; Social insurance; Political attitudes; Unemployment